Bad suffixes : morphological Pejoration in Old Sicilian - Egle Mocciaro; Roberta Romeo (Études romanes de Brno)
The article describes some aspects of the evaluative morphology of Old Sicilian (14th–16th centuries), with a focus on suffixes that encode a pejorative meaning. Based on a survey of the ARTESIA corpus, we draw the semantic network of three suffixes inherited, as in other Romance languages, from Latin: -azzu, -a (< Lat. -ācĕus; cf. acquazza 'dirty water'), -astru, -a (< Lat. -āster; cf. figliastru 'stepson') and -uni, -a (< Lat. -(i)ō; cf. tuvagliuni 'rough tablecloth'). We adopted a semantic-pragmatic theoretical background, which allows us to describe the pejorative sense and, more generally, evaluative meanings as a strategy to indicate first of all a certain degree of deviation from a standard defined within a linguistic community. In this sense, evaluation is essentially a tool for organising linguistic categories in prototypical terms, that is, as having a centre and a periphery, in which increasingly marginal examples are placed.